Czasowniki „być” w języku portugalskim – problemy semantyczne a dydaktyka - Tomalak, Katarzyna (Investigationes Linguisticae, 2009)
The process of teaching a foreign language usually begins with an introduction of one of the key verbs - “to be”. There are languages with two verbs “to be” like Portuguese: “ser” and “estar”. The article below tries to solve the problem of semantic distinction of the verbs and presents a few examples of didactic methods helpful in teaching the verbs “to be” in Portuguese.